Identity multiplicity among the Muslim second generation in European cities: Where are religious and ethnic identities compatible or conflicting with civic identities? - Fenella Fleischmann; Karen Phalet (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
Drawing on recent cross-nationally comparative survey data of the Turkish and Moroccan second generation in five European cities, this study examines the patterns of identification with ethnic, religious, national and city identities. We take a comparative perspective and analyse data from five cities (Amsterdam, Rotterdam, Antwerp, Brussels and Stockholm) that differ markedly in their policy approach to the integration of immigrants, the socio-economic position of the second generation and the political climate confronting ethnic and religious minorities. The analysis focuses on the question of how the Turkish and Moroccan second generation combines their ethnic and religious minority identities with identification with the country and city of residence. As European national identities are - to a greater extent than is the case for US American national identity - implicitly tied to and appropriated by the national majority group, we hypothesise that national identities will be non-inclusive of ethnic and religious identification, thus resulting in a negative correlation between Dutch/Belgian/Swedish identity on the one hand and Turkish/Moroccan and Muslim identities on the other. In contrast, we expect a positive correlation with identification with the city of residence, as Europe's cities are more diverse in terms of their population composition, have a more cosmopolitan outlook and are to a lesser extent dominated by one group of the population than the nationstates in which they are located. Secondly, we hypothesise that distinct identification patterns will be related to the modes of incorporation of the second generation, such that identity compatibility (i.e., positive associations between ethnic and religious identities on the one hand and national and city identities on the other) instead of identity conflict (i.e., negative associations) will be more often found in more favourable contexts of reception. – – Das Paper analysiert die Identifikationsmuster der türkischen und marokkanischen zweiten Einwanderergeneration in vergleichender Perspektive auf Basis von neuen ländervergleichenden Umfragedaten in fünf europäischen Städten in drei Ländern (Amsterdam, Rotterdam, Antwerpen, Brüssel und Stockholm). Diese unterscheiden sich deutlich in ihrer Einwanderungs- und Integrationspolitik, aber auch in der sozioökonomischen Position der zweiten Generation und in dem Maß der politischen Polarisierung rundum die Themen Immigration und Integration. Daraus ergeben sich länder- und städtespezifische modes of incorporation, die hier in Bezug zu den Identifikationsmustern der zweiten Generation gesetzt werden. Dabei richten wir uns vor allem auf die Zusammenhänge zwischen ethnischer und religiöser Identifikation auf der einen Seite - als Identitäten die die türkische und marokkanische zweite Generation von der Mehrheitsgesellschaft unterscheiden - und nationaler (d.h., niederländischer, belgischer und schwedischer) und Städte- Identifikation (z.B. Amsterdamer) - als Identitäten die mit der Mehrheitsgesellschaft geteilt werden. Da europäische nationale Identitäten stärker als dies in den USA der Fall ist von den ethnischen und religiösen Merkmalen der Mehrheitsgesellschaft bestimmt werden und daher ethnische und religiöse Minderheiten eher ausschließen, erwarten wir einen negativen Zusammenhang zwischen nationaler Identifikation auf der einen, und ethnischer und religiöser Identifikation auf der anderen Seite. Im Gegensatz dazu erwarten wir positive Zusammenhänge mit der Identifikation mit der Stadt, da europäische Städte im Vergleich zu den sie umringenden Ländern Zentren ethnischer und kultureller Vielfalt sind und ihre Identität daher weniger von einer einzelnen Gruppe dominiert wird. Aus vergleichender Perspektive erwarten wir, dass die Identifikationsmuster der zweiten Generation die modes of incorporation in den jeweiligen Kontexten widerspiegeln, so dass in für Einwanderer der zweiten Generation günstigeren Kontexten Identitäten eher kompatibel sind (d.h., positiv korrelieren) und sich seltener in Konflikt miteinander befinden (d.h. negativ korrelieren).
Keywords: 300; identification; identity multiplicity; second generation; Muslims; Europe; Identifikation; Identität; Multiplizität; zweite Generation; Muslime; Europa